Ambulatory heart rate range predicts mode-specific mortality and hospitalisation in chronic heart failure. Issue 3 (16th December 2015) - Cubbon, Richard M; Ruff, Naomi; Groves, David; Eleuteri, Antonio; Denby, Christine; Kearney, Lorraine; Ali, Noman; Walker, Andrew M N; Jamil, Haqeel; Gierula, John; Gale, Chris P; Batin, Phillip D; et al.
Abstract : Objective: We aimed to define the prognostic value of the heart rate range during a 24 h period in patients with chronic heart failure (CHF). Methods: Prospective observational cohort study of 791 patients with CHF associated with left ventricular systolic dysfunction. Mode-specific mortality and hospitalisation were linked with ambulatory heart rate range (AHRR; calculated as maximum minus minimum heart rate using 24 h Holter monitor data, including paced and non-sinus complexes) in univariate and multivariate analyses. Findings were then corroborated in a validation cohort of 408 patients with CHF with preserved or reduced left ventricular ejection fraction. Results: After a mean 4.1 years of follow-up, increasing AHRR was associated with reduced risk of all-cause, sudden, non-cardiovascular and progressive heart failure death in univariate analyses. After accounting for characteristics that differed between groups above and below median AHRR using multivariate analysis, AHRR remained strongly associated with all-cause mortality (HR 0.991/bpm increase in AHRR (95% CI 0.999 to 0.982); p=0.046). AHRR was not associated with the risk of any non-elective hospitalisation, but was associated with heart-failure-related hospitalisation. AHRR was modestly associated with the SD of normal-to-normal beats (R 2 =0.2; p<0.001) and with peak exercise-test heart rate (R 2 =0.33; p<0.001). Analysis of the validation cohort revealed AHRR to be associated with all-cause and mode-specific death as described in the derivation cohort. Conclusions: AHRR is a novel and readily available prognosticator in patients with CHF, which may reflect autonomic tone and exercise capacity.